2017
DOI: 10.1016/j.dld.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of gluten free diet in potential coeliac disease in adult population

Abstract: Although PCD with normal mucosa seems to be a milder disease, the continuation of GCD places patients at a high risk of developing villous atrophy and IMD compared to commencement of GFD. Adult PCD patients should start GFD even if not symptomatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In accordance with current guidelines, CD diagnosis was made in the presence of Marsh ≥ 2 histology associated with both anti‐tissue transglutaminase (a‐tTG) IgA > 7 U/mL and positive anti‐endomysial (EMA) antibodies . All subjects with positive serology but negative histology (Marsh 0 or 1) underwent further investigations for genetic susceptibility and were diagnosed as “potential” CD in the presence of HLA DQ2/DQ8 . Histopathological findings were graded according to Marsh et al…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with current guidelines, CD diagnosis was made in the presence of Marsh ≥ 2 histology associated with both anti‐tissue transglutaminase (a‐tTG) IgA > 7 U/mL and positive anti‐endomysial (EMA) antibodies . All subjects with positive serology but negative histology (Marsh 0 or 1) underwent further investigations for genetic susceptibility and were diagnosed as “potential” CD in the presence of HLA DQ2/DQ8 . Histopathological findings were graded according to Marsh et al…”
Section: Methodsmentioning
confidence: 99%
“…Imperatore et al. showed that over a six‐year period, 69% of asymptomatic potential CD developed CD‐related symptoms 38 . In our study, all anti‐EMA positive donors but one, were diagnosed with CD (from which one patient refused biopsy but is most probably CD).…”
Section: Discussionmentioning
confidence: 44%
“…37 Imperatore et al showed that over a six-year period, 69% of asymptomatic potential CD developed CDrelated symptoms. 38 In our study, all anti-EMA positive donors but one, were diagnosed with CD (from which one patient refused biopsy but is most probably CD). Our findings reiterate the importance of follow-up serology and of confirmatory anti-EMA testing in establishing the true prevalence of CD autoimmunity and of CD when studying populations.…”
Section: Discussionmentioning
confidence: 54%
“…Some patients were affected by non-classical CD – they either experienced mild gastrointestinal symptoms without clear signs of malabsorption, or presented with other extra-intestinal conditions (chronic fatigue, chronic migraine, peripheral neuropathy, chronic hypertransaminasemia, reduced bone mass and bone fractures, dermatitis herpetiformis, etc.) [28, 29]. …”
Section: Methodsmentioning
confidence: 99%